Liquid-phase synthesis of magnesium phosphates in the presence of gallic acid - O.N. Musskaya; V.K. Krut’ko; I.E. Glazov; E.N. Krutsko; A.I. Kulak (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов)
In aqueous solutions of magnesium chloride and sodium dihydrogen phosphate at Mg/P molar ratios of 1,0-1,5 and pH of 5-7 in the presence of gallic acid, crystalline hydrates of magnesium hydrophosphate (newberyte – MgHPO4ꞏ3H2O) and orthophosphate (Mg3(PO4)2ꞏ22H2O) were obtained, which after heating at 800°C transformed into pyrophosphates (Mg2P2O7). X-ray phase and thermal analysis methods, as well as infared spectroscopy, showed that the presence of an organic additive in the liquid-phase synthesis of magnesium phosphates does not lead to a noticeable change in the phase composition of the reaction products. It was revealed that gallic acid affects the formation of the structure of crystalline hydrates depending on the Mg/P molar ratio. It was found that with prolonged maturation of the sediments (over 6 months), the size of the unit cell of magnesium phosphates decreases. The obtained magnesium phosphate powders modified with gallic acid exhibit redox activity and are promising for use in biomaterials as resorbable components with antioxidant properties.